Involving customers and users in university-industry collaboration - Kunttu, Leena; Takala, Josu (The International Society for Professional Innovation Management (ISPIM), 2019)
High-technology firms are increasingly engaging in collaborative relationships with universities to transfer academic knowledge for industrial purposes or to jointly develop valuable new knowledge. The university-industry collaboration typically focuses on the early stages of a product development process, where new ideas and innovations are being developed. On the other hand, the interaction between the firm and its customers takes place during the commercialization of new innovations. For this reason, customer insights should be included to a greater extent in university-industry collaboration projects. Based on a case study comprising five long-term university-industry collaborations in Finland, this paper demonstrates how the involvement of end users and industrial customers in university-industry collaborations can contribute to both the early and late phases of the product development process. This paper highlights the collaboration practices involving end users and customers that facilitate the commercialization of the university-industry collaboration.
Keywords: commercialization; university-industry collaboration; customer involvement; user involvement; fi=Tuotantotalous|en=Industrial Management|